Prospect Theory-Based Optimal Bidding Model of a Prosumer in the Power Market - Ying Wang; Ling Zhang; Qia Ding; Kaifeng Zhang (IEEE Access, 2020)
This paper proposes a prospect theory (PT)-based bidding model of a prosumer in the power market. Unlike existing efforts of the bidding model that assume the rational behavior of the prosumers, the model incorporates irrationality and individual preferences to capture the prosumer-related subjective perceptions on the bidding results. Considering the impacts of the bidding rules of the power market, we build up the PT-based bidding models with 1-segment and multi-segment bidding rules, respectively. A case study with four different prosumers, i.e., rational, conservative, neutral, and aggressive prosumers is conducted, and the simulation results between expected value theory-based and the PT-based methods are compared. Simulation results validate the effectiveness of the proposed method.